2010
DOI: 10.1016/j.cpcardiol.2010.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Monitoring of Abdominal Aortic Aneurysm: Current Status and Future Prospects

Abstract: Abdominal aortic aneurysm (AAA) remains an important cause of morbidity and mortality in elderly men, and prevalence is predicted to increase in parallel with a global ageing population. AAA is commonly asymptomatic, and in the absence of routine screening, diagnosis is usually incidental when imaging to assess unrelated medical complaints. In the absence of approved diagnostic and prognostic markers, AAAs are monitored conservatively via medical imaging until aortic diameter approaches 50-55mm and surgical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
152
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(156 citation statements)
references
References 196 publications
(228 reference statements)
3
152
0
1
Order By: Relevance
“…During the early stages of AAA formation, VSMC undergo phenotypic switch which is characterized by downregulation of VSMC differentiation markers, such as SM‐22α, α‐SMA as well as an increase in proliferation, migration, and synthesis of extracellular matrix proteins 2, 26. In our study, we observed decreased levels of α‐SMA and SM‐22α by immunohistochemistry in human AAA and PPE‐induced AAA tissues.…”
Section: Discussionsupporting
confidence: 57%
“…During the early stages of AAA formation, VSMC undergo phenotypic switch which is characterized by downregulation of VSMC differentiation markers, such as SM‐22α, α‐SMA as well as an increase in proliferation, migration, and synthesis of extracellular matrix proteins 2, 26. In our study, we observed decreased levels of α‐SMA and SM‐22α by immunohistochemistry in human AAA and PPE‐induced AAA tissues.…”
Section: Discussionsupporting
confidence: 57%
“…On the contrary, an elective AAA repair, recommended in most patients with an abdominal aortic diameter exceeding 50-55 mm or rapid growth (> 1 cm/y), is associated with a mortality risk of 2% to 6% (Kurvers at al., 2003;Sakalihasan et al, 2005). Health organizations recently recommended one-time screening for AAA by ultrasonography for men aged between 65 and 75 years with a smoking history, thereby reducing AAA related mortality rates by 50% (Cosford & Leng, 2007;Ehlers et al, 2008;Ferket et al, 2011;Moxon et al, 2010;Takagi et al, 2010). However, they advised against screening in men below 65 and over 75 years, and in women, since the number of AAArelated deaths that can be prevented by screening these populations is too small.…”
Section: Introductionmentioning
confidence: 99%
“…Due to current investigation of markers associated with AAA, targeted ultrasound imaging may be a future option (Moxon et al, 2010;Villanueva 2008). With increased knowledge of pathophysiological mechanisms, pharmacotherapy or gene therapy may be available for stabilization of aneurysms (Baxter et al, 2008;Cooper et al, 2009;Golledge et al, 2009;Raffetto & Khalil, 2008;Twine & Williams, 2011).…”
Section: Functional and Molecular Imagingmentioning
confidence: 99%